Przygotowania do kreowania wizerunków Polski w okresie prezydencji w Radzie Unii Europejskiej = Shaping the image of Poland during the presidency in the Council of the European Union ? the preparatory stage - Glinka, Kamil (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Presidency in the Council of the European Union creates conditions to shape the image of a state. This regularity is confirmed in the case of Poland as well. Especially if one takes into account the fact that Poland is the first large state of the ?new EU?, which faced the task to preside the works of the EU Council. The main aim of the article is to discuss the preparatory stage to the process of shaping our state image during Polish presidency in the EU Council. It is therefore justified to illustrate activities which constitute these preparation as well as to discuss the activities undertaken by proper institutions. Especially if one considers their dual orientation. First of all, the absence of proper experience of Poland in the organization of the process of shaping its own image. Secondly, there exist the formal-legal proposals deciding on the character of the Presidency accepted on the basis of the Treaty of Lisbon.
Keywords: Unia Europejska; Rada Unii Europejskiej; prezydencja